Evaluation of Key Risk Factors Associated with Postoperative Complications in Colorectal Cancer Surgery - Silviu Stefan Marginean; Mihai Zurzu; Dragos Garofil; Anca Tigora; Vlad Paic; Mircea Bratucu; Florian Popa; Valeriu Surlin; Dan Cartu; Victor Strambu; Petru Adrian Radu (Journal of Mind and Medical Sciences, 2025)
Background: Colorectal surgery remains a cornerstone in the management of colorectal cancer, yet postoperative complications continue to impact surgical outcomes. This study investigates key risk factors influencing morbidity, focusing on patient comorbidities, tumor characteristics, surgical techniques, and anastomotic methods. Methods: A retrospective analysis was conducted on 195 patients who underwent colorectal cancer surgery between January 2021 and December 2024 at the Clinical Hospital of Nephrology “Carol Davila”. Variables analyzed included patient demographics, comorbidities, tumor staging, surgical approach, and postoperative complications. Statistical methods included chi-square tests and multivariate logistic regression (significance threshold: p < 0.05). Results: The overall complication rate was 21%, with anastomotic leakage observed in 8.2% of cases. Significant risk factors for morbidity included cardiovascular disease (p = 0.001), chronic respiratory failure (p = 0.003), and chronic renal failure (p = 0.002). Laparoscopic surgery had a lower complication rate (7.1%) than open surgery (28%) (p = 0.003). Mechanical anastomosis showed lower complication rates than manual suturing (p = 0.009). Left-sided resections were associated with higher morbidity than right-sided procedures (p = 0.013). Conclusions: Optimizing colorectal surgery outcomes requires personalized perioperative strategies. Laparoscopic approaches and mechanical anastomosis significantly reduce complications. Further multicenter studies are needed to confirm these findings and enhance surgical guidelines.